Elastic proton scattering on 13С and 15С nuclei in the diffraction theory - Zhusupov, M.A.; Ibrayeva, Ye.T.; Kabatayeva, R.S.; Zhaksybekova, K.A.; Temirbayev, D.; Kazhykenov, Sh. (Recent Contributions to Physics, 2017)
There is a calculation of the differential cross sections of proton scattering on 13С and 15С nuclei at energy of 1 GeV with the shell model wave functions in the framework of the Glauber theory in the study. The single, double and triple collisions have been taken into account in the multiple scattering operator. The role of each term of the series and their interference in the differential cross section have been estimated. It is shown that for a description of the cross sections in a wide angle/momentum transfer range it is necessary to consider not only the first, but the higher scattering orders. Having calculated the contribution into the differential cross sections from the first three terms of the series of multiple scattering, the authors showed that the single scattering dominates at the very small angles (until 12 degrees), double – in the range of the second maximum (from 12 to 20 degrees), triple – in the range of the third maximum at 20° and more degrees. In the points of intersection of the different orders in the differential cross sections there appear the typical interference minimums since the series of multiple scattering is a sign-alternating one and the cross terms are subtracted from the total sum.